الميول البحثية لدى طلبة المركز الوطني للمتميّزين دراسة ميدانية باستخدام قائمة سترونغ للميول المهنية في محافظة اللاذقية - حاتم فهد (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
هدفَ البحث الحالي إلى التعرّف على الميول البحثية لدى طلبة المركز الوطني للمتميزين في اللاذقية باستخدام مقياس الميل البحثي كأحد مقاييس الميول المهنية الموجودة في قائمة سترونغ للميول, والذي تم تقنينه من قِبل الباحث, وقد تم تطبيق المقياس على عيّنة مؤلفة من 80 طالباً وطالبة من طلبة المركز الوطني للمتميّزين, وخلصت نتائج البحث إلى عدم وجود فروق بين أفراد العينّة في الميل البحثي والمقاييس الأساسية التابعة له, باستثناء وجود فروق لصالح الإناث في مقياس العلم. The aim of current research is to identify the research tendencies among the students of the National Center for the Distinguished in Lattakia, by using a research inclinometer as a measure occupational orientations in the Strong Interest Inventory of interests, which was codified (standardized) by the researcher, and the scale has been applied to a sample of 80 students from the National Center for the Distinguished, and the search results found no differences between respondents in the investigative tendency and its key metrics, except for differences in favor of females in science scale.